Plan de exportación de chaquetas de cuero para la empresa PATRICK´S de la ciudad de Cotacachi - Chávez, Claudia X. (2017)
The present work has as main objective to design a plan of export for the company to Patrick´s will be able to internationalize the leather jackets, In addition to arrive directly to the customer, without the use of intermediaries, also providing the company with knowledge about the processes and export documents.